Effectiveness of yoga exercise and the provision of vitamin E to decreasing dysmenorrhea - Oktavia, Nike Sari; Doni, Alsri Windra; Sakinah, Ella (Jurnal Kesehatan Ibu dan Anak, 2019)
Dysmenorrhea is an excessive disorder during menstruation which causes women to recover or engage in activities which results in increased ability and affects academic and social activities. In non-pharmacology, yoga exercises can increase the endorphin hormone in the body so that it can reduce pain during menstruation. And vitamin E has a role in inhibiting prostaglandin synthesis, while prostaglandin is associated with the onset of pain when attacked. The purpose of this research was to learn how yoga exercises and the provision of vitamin E to reduce dysmenorrhea in the female. This type of research was pre-experimental with two groups of pretest-posttest design. The population of this research was all of the S-1 female students of the Health Promotion Program at the Poltekkes Kemenkes Padang with a sample of 32 people. Data was collected by filling in the numerical rating scale. Data analysis using dependent T-Test and independent T-Test. The results of the independent T-Test were obtained on average before and after yoga practice (mean=1.438, t=11.223, p= 0.00) and after the provision vitamin E (mean=2.688, t=17.885, p= 0.00). The results of the dependent T-Test were obtained on yoga practice and the provision vitamin E (p= 0.039). The conclusions in this research are yoga exercises and the provision of vitamin E are equally effective in reducing dysmenorrhea. But, the provision of vitamin E has more effective in reducing dysmenorrhea compared to yoga exercises. By this research, sufferers can use Vitamin E as an alternative in reducing dysmenorrhea.